2014
DOI: 10.1021/ma402396f
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Cross-Nucleation in Isotactic Poly(1-butene)

Abstract: During crystallization of polymorphic substances, a daughter phase may nucleate on the surface of a previously present polymorph: this crystallization scheme has been denoted as cross-nucleation. While several extensive studies exist for small organic molecules, analogous reports for semicrystalline polymers are scarce. Hereby we present the first determination of cross-nucleation kinetics for crystallizable macromolecules. The melt of isotactic poly(1-butene) was seeded with Form I spherulites through an in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 43 publications
2
77
0
Order By: Relevance
“…it can be considered that the concentration of heterogeneous nuclei is constant at a given temperature within a certain time interval, cross-nucleation on Form I spherulites is 'pseudo-homogeneous', with the surface density of Form II nuclei linearly increasing with time. 24,27,28 Moreover, the amount of seed surface available for cross-nucleation is similarly time-dependent, being progressively occupied by Form II morphologies growing on the substrate or impinging from neighboring seeds. Therefore, the application of a simple crystallization model, such as the Avrami, is meaningless.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…it can be considered that the concentration of heterogeneous nuclei is constant at a given temperature within a certain time interval, cross-nucleation on Form I spherulites is 'pseudo-homogeneous', with the surface density of Form II nuclei linearly increasing with time. 24,27,28 Moreover, the amount of seed surface available for cross-nucleation is similarly time-dependent, being progressively occupied by Form II morphologies growing on the substrate or impinging from neighboring seeds. Therefore, the application of a simple crystallization model, such as the Avrami, is meaningless.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Cavallo and Alfonso have shown that many more overlooked examples exist in the polymer crystallization literature. [21][22][23] Moreover, systematic extension of a quantitative approach to cross-nucleation to different macromolecules (isotactic poly(1-butene), polypivalolactone and isotactic polypropylene) [23][24][25][26][27][28] allowed us to understand that the nucleation of one polymorph on another can be regarded as a special case of heterogeneous nucleation, unless the parent phase grows at rates comparable to those of the daughter polymorph. 24,28 All the wealth of information so far obtained on cross-nucleation has been exclusively gathered by optical microscopy analysis of the developing morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Then the samples were quickly cooled down to room temperature and aged for more than 1 month in order to completely transform the original Form II crystals into Form I. It should be noted that, according to previously adopted procedures for cross‐nucleation studies in PB‐1, a dual morphology is produced . Indeed, low melting temperature crystals of Form I, formed during quenching to room temperature, are essential for having molten PB‐1 in contact with crystalline Form I seeds (with higher melting temperature) …”
Section: Methodsmentioning
confidence: 99%
“…It was found that nucleation rate at constant undercooling increased by 60 times with decreasing Δ σ/σ from 0.23 to 0.13, which confirms that Δ σ is extremely sensitive for detecting the nucleating ability of a substrate . For what concerns cross‐nucleation, although the kinetics of the process has already been studied for several systems, a detailed description based on Δ σ calculation was not extensively applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation